The Analysis of Types and Functions of Interjections Used in Webtoon Digital Comic - Nurhalima Tanjung; Yetty Zainil; Delvi Wahyuni (Universitas Negeri Padang, 2020)
The aims of this research is to describe the types and function of interjections used in Webtoon Digital Comic, the differences of used between primary that has 4 subdivided and secondary interjection. The type of this research was a descriptive qualitative research. The data were taken from five genre of Webtoon Digital Comic, they were drama, fantasy, romance, sci-fi and comedy. The data were collected by download 1 title in each 5 genres and then used highlighter to identifying the types and function of interjection. The researcher used table instrument to categories the types and function of interjection used. It is found there are primary and secondary interjection, but the most commonly used is primary interjection that has appeared with 333 (65.81%), while for secondary interjection it just appeared in 173 (34,18%). The results showed that in primary interjection the most frequently found was Expressive function with 167 times, followed by Phatic that has frequency 95 times, and the lowest frequency was comes from Conative that appeared 71 times. Furthermore, in Secondary Interjection result showed there was no significance difference in the use of noun, adjectives, verb and adverb functions.